50 de ani fără Dumnezeu: Apocalipsa şi apocriful în „Un singur cer deasupra lor” al Ruxandrei Cesereanu - Tórz, Marta (Studia Romanica Posnaniensia, 2014)
This paper proposes the reading of Ruxandra Ceseranu’s novel Un singur cer deasupra lor as a modern apocrypha presenting a historiosophic vision of Romania’s fate in the second half of the 20th century with the use of apocalyptic themes and symbolic imagery. The analysis consists of tracing references to the Book of Revelation which is a key element to the interpretation of the novel, and to other biblical books and themes. The analysis is supplemented with an attempt at describing the most significant archetypical and cultural symbols, and the remnants of bygone traditions that provide the second reading to those historically-grounded stories. References to folk tales based on Christian imaginary world further strengthen the proposition of the apocryphal nature of the work. The additional argument supporting my thesis is the polyphonic and multilayer structure of the novel that combines subjective visions and mythical interpretations with the factual layer, and the use of palimpsest technique consisting of interweaving texts of other authors into the main narration. The paper does not address the question of the conformity of the literary vision with the source documents and historical prototypes of certain episodes and persons. Those matters were partly commented on by the author in the afterword.